2019
DOI: 10.1021/acs.orglett.9b01847
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free One-Pot Synthesis of Unsymmetrical Five- and Six-Membered Sulfur-Annulated Heterocyclic Perylene Diimides for Electron-Transporting Property

Abstract: A novel unsymmetrical fiveand six-membered sulfur-annulated heterocyclic perylene diimides (PDI) derivative was obtained by a one-pot and catalyst-free synthesis in a high yield. The unsymmetrical PDI exhibits a noteworthy bathochromic shift absorption of up to 700 nm and a lowlying lowest unoccupied molecular orbital level of −3.99 eV. The compound owns a complete planar structure and a high electron mobility of 4.8 × 10 −3 cm 2 V −1 s −1 in solutionprocessable top-gate/bottom-contact organic field-effect tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…[24] Notably, dinitroperylene 66 b reacted with sulfur at lower temperature to provide thiophene product 68. [25] The degree of sulfuration seemed strongly dependent on the reaction temperature. This reaction was in agreement with the previous result observed with parent tetracarboxylic acid derivative.…”
Section: Scheme 19mentioning
confidence: 99%
“…[24] Notably, dinitroperylene 66 b reacted with sulfur at lower temperature to provide thiophene product 68. [25] The degree of sulfuration seemed strongly dependent on the reaction temperature. This reaction was in agreement with the previous result observed with parent tetracarboxylic acid derivative.…”
Section: Scheme 19mentioning
confidence: 99%
“…Following the same sequential synthesis, S-annulated PDIs 14 and 15 were nitrated and bisbridged, affording unsymmetrical S-PDI-2S 21 in both cases in 76% yield over two steps [60]. In the same work, a one-pot synthesis of the same product was also reported from a mixture of 1,6 and 1,7dinitro-PDIs 4 in 80% yield.…”
Section: Access To Core-extended Annulated Pdimentioning
confidence: 76%
“…Notably, at a high temperature in DMF, only thiophene-annulated PDI 14 was formed in 71% yield [38]. L. Chen et al reported the formation of derivatives 14 and 15 in 34% and 42% yields respectively, by heating the reaction in DMF at 120 • C [60]. On the other hand, bubbling O 2 or adding selenium powder into 1-nitroPDI 5 in NMP at 180-190 • C led to O-annulated PDI 16 [61].…”
Section: Access To Core-extended Annulated Pdimentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al presented the first example of a one-pot synthesis of an unsymmetrical sulfur-fused perylene diimide derivative (Scheme 13). 30 Here, the dinitro-PDI reacted with sulfur at 80 °C to provide monothiophene-fused PDI in 80% yield. Continuing to increase the reaction temperature to 120 °C, an unsymmetrical five-and six-membered sulfurannulated heterocyclic PDI compound was obtained.…”
Section: Scheme 12 Synthesis Of Thiophene-fused Pdis Using Smentioning
confidence: 99%